CT screening for lung cancer: Importance of emphysema for never smokers and smokers. Issue 1 (April 2015) - Henschke, Claudia I.; Yip, Rowena; Boffetta, Paolo; Markowitz, Steven; Miller, Albert; Hanaoka, Takaomi; Wu, Ning; Zulueta, Javier J.; Yankelevitz, David F.; for the I-ELCAP Investigators, 1
Highlights Lung cancer prevalence increased when emphysema was identified on low-dose CT scan. Never smokers with CT evidence of emphysema are at the same risk of lung cancer as a smoker. Prevalence of lung cancer was similar among smokers and never smokers below age 50.